Superhydrophobic surfaces review: Functional application, fabrication techniques and limitations. Issue 1 (May 2019) - Manoharan, Kapil; Bhattacharya, Shantanu
Abstract: Over the years, researchers have been working to mimic the nature by inducing superhydrophobic properties into a variety of material surfaces so that they exhibit non-wetting properties. Many diverse applications have been found in the fields, such as space and aerospace, defence, automotive, biomedical applications and engineering, sensors, apparels, and so on. Superhydrophobic surfaces repel water generally due to their surface texture or chemical properties. In this article, we focus on the functional applications of the superhydrophobic surfaces, and state-of-the-art fabrication technologies and processes, and the limitations of these processes to generate the superhydrophobic surfaces have been developed over the years.